Anisotropy Enhanced Phase Separation in Polymer Dispersed Liquid Crystals - Benmouna, Farida; Benmouna, Mustapha (Journal of Research Updates in Polymer Science, 2017)
Phase separated blends of polymers and low molecular weight liquid crystals, commonly known as polymer dispersed liquid crystals in short PDLCs, are investigated. These materials offer a realm of applications in modern technologies, including sensors, commutable windows, display devices and telecommunication systems. A particular attention is given to the effects of anisotropy of the liquid crystal on the phase behavior under equilibrium and non equilibrium conditions. The theoretical formalism used is based on the lattice model of isotropic mixing, combined with standards theories of nematic and smectic-A orders. Considering the equilibrium phase behavior, we find that the nematic order enhances the polymer / solvent phase separation, and that the osmotic pressure shows substantial changes for relatively small polymer volume fractions. We find that the anisotropy enhanced phase separation is more pronounced for a smectic-A liquid crystal, and the miscibility gap is widened. The kinetics of swelling by nematic LCs is examined using a linear solvent diffusion process, with a rate of swelling directly related to the derivative of the osmotic pressure. An abrupt swelling / de-swelling transition is found, due to overwhelming effects of the anisotropic interaction beyond the threshold LC concentration. Anisotropy enhanced phase separation is also investigated in the method of synthesis based on the polymerization induced phase separation mechanism. We find that the kinetics of separation during early stages of polymerization is faster, due to the anisotropic interaction of the low molecular weight solvent. The kinetics speed up is favored by the long range viscous flow effects due to hydrodynamic interactions. A limited selection of experimental data in the literature is chosen to validate some theoretical predictions obtained from the present formalisms.